Computerbased Interpretations of Literary Texts: a Real Gain in Knowledge? Theoretical Preliminary Considerations on a Digital Map of German-language Literature from Southeast Europe - Spiridon-Șerbu, Claudia (Universitatea Transilvania Brasov, 2024)
Against the backdrop of ongoing debates regarding the effectiveness of using digital tools for gaining insights into literary studies, the objective of this paper is to examine closely frequently questioned aspects of computer-assisted text analysis. It brings forward arguments from literary criticism and presents methodological considerations related to an ongoing project at the Department of Literature and Cultural Studies at the Faculty of Philology at Transylvania University in Kronstadt.
Keywords: Computer-Assisted Text Analysis; Literary Cartography; Eastern European Turn in German-Language Literature